Eustasy and Chrono-correlations: Facts and Theories with Examples from the Ordovician - Fähræus, Lars (Geoscience Canada, 1996)
Summary During the past 15 years a very rapidly increasing general interest in eustasy and its causes and, in particular, highly detailed chrono-correlations utilizing the Phanerozoic sea-level curves compiled by Peter Vail and coworkers at Exxon have resulted in a large number of publications, including several using presumed Ordovician eustatic events for chrono-correlations. However, facts and theory argue against the possibility of recognizing synchronous sea-level fluctuations in a set of widely separated stratigraphie sections (see also Paleoscene 16: Miall, 1994). There are simply too many factors influencing the shape of the ocean geoid, the recording of sea-level changes on the margins of continents, and fossil and/or radiometrically based time constraints. These factors make it impossible to identify and discriminate individual eustatic events with the precision necessary for detailed high-resolution chrono-correlations in pre-Tertiary successions. Instead, fossils and radiometric data remain the decisive tools for detailed regional and worldwide chrono-correlations.